Biology and evolution of the mollusca. Volume two - Ponder, W. F.; Lindberg, David R., 1948-; Ponder, Juliet M. (Boca Raton, FL : CRC Press, 2020)
This volume provides individual treatments of the major molluscan taxa. Each chapter provides an overview of the evolution, phylogeny and classification of a group of molluscs, as well as more specific and detailed coverage of their biology (reproduction, feeding and digestion, excretion, respiration etc.), their long fossil record and aspects of their natural history. The book is illustrated with hundreds of colour figures. In both volumes, concepts are summarised in colour-coded illustrations.
OCLC-licensed vendor bibliographic record.
Keywords: Mollusks; Mollusks -- Evolution